FIRM CHARACTERISTIC, OWNERSHIP STRUCTURE AND VOLUNTARY DISCLOSURE: A Study of Indonesian listed Manufacturing Firm - Wirmie Eka Putra; Indra Lila Kusuma; Maya Widyana Dewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study is entitled Analysis of Factors Affecting Voluntary Disclosure (Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange Period 2017-2019). This study aims to examine the effect of leverage, liquidity, profitability, company size, managerial ownership, and institutional ownership on voluntary disclosure. Data analysis methods used are multiple regression analysis, simultaneous significance test and partial significance test. Simultaneous significance test results show that leverage, liquidity, profitability, company size, managerial ownership, and institutional ownership have a significant effect on voluntary disclosure. The results of the partial significance test show that leverage and firm size affect voluntary disclosure, while liquidity, profitability, managerial ownership, and institutional ownership do not affect voluntary disclosure. Keywords: voluntary disclosure, leverage, liquidity, profitability, company size, managerial ownership, institutional ownership